2008
DOI: 10.2111/07-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance of a Stock-Watering Pond in the Flint Hills of Kansas

Abstract: Small ponds are often the main source of drinking water for grazing livestock. The hydrology of these ponds must be understood so impoundments can be located, designed, and managed to avoid water shortages during dry weather. A study was conducted to measure the water balance of a stock-watering pond in the Flint Hills region of east-central Kansas from June 2005 to October 2006. The 0.35-ha pond supplied water to 250-kg yearling steers in a 65-ha pasture of native tallgrass prairie. Evaporation, depth change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…For example, vigorous natural convection on the water side could easily change the surface temperature, and hence evaporation rate, however such a change in T s is accounted for in the variables q wv;s and q s used in Eqs. (8) and (10), which are in turn used in the present definitions of Sh and Ra. On the other hand, one might argue that for a given average T s , two different tanks having different water-side Rayleigh numbers due to different depths will have different water-side turbulence intensities giving, for example, a different value for the root mean square of T s .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, vigorous natural convection on the water side could easily change the surface temperature, and hence evaporation rate, however such a change in T s is accounted for in the variables q wv;s and q s used in Eqs. (8) and (10), which are in turn used in the present definitions of Sh and Ra. On the other hand, one might argue that for a given average T s , two different tanks having different water-side Rayleigh numbers due to different depths will have different water-side turbulence intensities giving, for example, a different value for the root mean square of T s .…”
Section: Discussionmentioning
confidence: 99%
“…The method for obtaining the densities used in Eqs. (8) and (10) follows the procedure presented in Sparrow et al [18]. The density of water vapor in the air is obtained from:…”
Section: Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, estimates of the annual water supply were calculated for cattle in the Flint Hills region of Kansas considering seasonal evaporation and throughflow (Duesterhaus et al 2008). For an animal with a mean weight of 250 kg, cattle require on average 30 L per day per individual, but this amount varied over time (Duesterhaus et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, estimates of the annual water supply were calculated for cattle in the Flint Hills region of Kansas considering seasonal evaporation and throughflow (Duesterhaus et al 2008). For an animal with a mean weight of 250 kg, cattle require on average 30 L per day per individual, but this amount varied over time (Duesterhaus et al 2008). In a study of the comparative ecology of cattle and bison in tallgrass prairie in Oklahoma, USA, Allred et al (2011) showed cattle foraging close to permanent water sources, while bison spent more time at greater distances from permanent water sources.…”
Section: Discussionmentioning
confidence: 99%